Book Title Prediction using the Moving Average Forecasting Method: Prediksi Judul Buku menggunakan Metode Moving Average Forecasting - Endraswari, Putri Mentari; Tou, Nurhaeka; Zaliman, Iski (Program Studi Informatika Fakultas Teknik Universitas Janabadra, 2024)
Libraries are oriented towards increasing user interest and reading culture as a source of information and inspiration. The library's main activity is borrowing books, so one measure of a library's success is the number of books borrowed. Library managers need to know which books users are interested in to predict book titles so that book data is more up-to-date. The prediction system currently implemented by libraries only relies on traditional predictions for frequently borrowed books, by setting the same number from month to month without any prior calculations, making it difficult to predict book titles accurately. This research aims to apply the Moving Average Forecasting Method to predict book titles in libraries based on borrowing logs. An estimated value for each book was obtained from experiments on data on borrowing 10 books in 14 months. This calculation is taken from the highest estimated value for each book based on the number of books borrowed each month. The higher estimated value of the resulting book indicates that the book is in great demand by users. If the resulting estimated value is low then the book is less popular with users.